Operation of SOFC Short-Stacks with Simulated Bio-Syngas: Influence of Model Tars Naphthalene and Phenol. Issue 12 (17th August 2020) - Hauser, Michael; Herrmann, Stephan; Hauck, Maximilian; Fendt, Sebastian; Lenser, Christian; Menzler, Norbert H.; Spliethoff, Hartmut
Abstract : Operation of solid oxide fuel cells (SOFCs) with bio-syngas from the gasification of biomass is a promising approach to highly efficient and sustainable power generation. At the same time, the coupling is challenging as several biogenic impurities in the bio-syngas have a negative effect on the SOFC. For this paper the impacts of the impurities naphthalene and phenol on SOFC short-stacks were investigated experimentally for the first time. The cell in the stacks were anode-supported SOFCs with Ni/YSZ anode. The experiments were performed at 700 °C under load with simulated bio-syngas consisting of hydrogen, carbon monoxide, carbon dioxide, methane and water vapor. 2 g Nm −3 of naphthalene (350 ppm) caused a pronounced voltage drop and an increase in cell temperature. By analysing the anode off-gas and recording of I–V-curves, it could be shown that naphthalene blocked the electrochemical hydrogen oxidation as well as the reforming of methane and the shift reaction of carbon monoxide. Up to 8 g Nm −3 of phenol (1900 ppm), on the other hand, led to carbon deposition and irreversibly damaged the structure of the anode substrate by metal dusting. This form of degradation was not visible in the electrochemical data during operation.